Current status on the diversity and abundance of ichneumonids (hymenoptera : ichneumonidae) in Kuala Lompat Forest Reserve, Pahang / Azizi, M.A. ... [et al.] - Abdullah, Mohammad Azizi; M. E, Yazid; Ayob, Mohammad Amizi; Yaakop, Salmah; A.B., Idris (2012)
The ichnuemonids (Hymennoptera: Ichneumonidae) are parasitic wasps which play a key role in maintaining insect population dynamics in forest and agricultural ecosystems. Due to this fact, some species are being used as important biological control agents of insect pests of economic importance and proved to be one of the best biological indicators of forest disturbance. As such, a study on the diversity and abundance of ichnuemonids (Hymennoptera: Ichneumonidae) in Kuala Lompat Forest Reserve, Pahang (KLFR) was conducted. In this study, the ichnuemonids were collected continuously for three months using Malaise trap. A total of five malaise traps were located at different plots in the surrounding area. The collected specimens were identified up to morphospecies level. Data was analyzed using Bio-DAP software to get the ecological indexes (ShannonWiener diversity Index (H'), the Evenness Index (E) and the Margalef Index (R')). A total of 350 individuals from 14 subfamilies and 45 morphospecies were successfully collected from KLFR. The subfamily collected were Adelognathinae, Anomaloninae, Campopleginae, Cremastinae, Cryptinae, Ichneumoninae, Lycorininae, Mesochorinae, Metopiinae, Ophioninae, Orthocentrinae, Phrudinae, Pimplinae and Poemeniinae. The ecological index values were 3.18, 0.85 and 7.51 for the H'. E' and R', respectively, indicating high ichneumonid species diversity and individual abundance at KLFR. The highest number of individuals and morphospecies collected was from the subfamily Cryptinae (123, 10) and followed by Pimplinae (104,9). However, further investigation should be conducted in the near future to measure human interventions, biotic and abiotic factors that influence the diversity and abundance of ichneumonids in KLFR.